Guidelines for legal representatives of children in civil matters - Carina du Toit (Pretoria University Law Press (PULP), 2016)
Guidelines for legal representatives of children in civil matters Editors: Ann Skelton and Carina du Toit 2016 ISBN: 978-1-920538-49-1 Pages: 28 Print version: Available Electronic version: Free PDF available